On the Basing-Point System: Comment - Haddock, David D. (American Economic Review, 1990)
In On the Basing-Point System, Bruce Benson, Melvin Greenhut, and George Norman (1990)1 properly correct a misunderstanding by Jacques Thisse and Xavier Vives (1988)2 concerning my 1982 paper on basing-point prices. But BGN then take exception with several of the conclusions I had reached, or that they thought I had reached. Although I have insufficient space to deal with all the points they raise, I will address the most important ones. In 1981 most economists believed that a model of profit-maximizing basing-point pricing would have to assume collusion. My model, as BGN seem to agree, showed that it need not; atomistic competition at one production site accompanied by local monpolies elsewhere may lead to basing-point pricing and freight absorption without collusion.3 Conversely, TV showed that the practice as observed empirically will not arise if all production sites contain noncooperative local monopolies. BGN establish yet another important theoretical result-noncooperative oligopoly at one site could generate the f.o.b. prices (or f.o.b. plus transport) that, in my model, led local monopolies elsewhere to adopt freight-absorbing basing-point prices. The three models would seem to be complements. I. A Paradox